Dysfunction of Collaborative Governance in the Handling Policy of Covid-19 at Jambi Province - Muhammad Ichsan Kabullah; Sudarmoko Sudarmoko; Hendri Koeswara; Fajri Rahman; Azwar Azwar (Institut Teknologi Sepuluh Nopember, 2021)
Current research on public administration has generally concluded that collaborative governance is a key factor to solve the contemporary crisis. This argument departs from the essence of a concept that brings state and private stakeholders together in policymaking. Through a case study in the Jambi Province, we find that the collaboration between local governments and society has useful in handle Covid-19 crisis because they may shared understanding to prioritize Covid-19 pandemic as common problem. At the same time, the religious tension also gave a positive impact for the collaboration. However, the collaboration performance has followed several challenges such as incompatible procedures, inequality for the same access between individuals, and intervention by local elites.